Scrupulosity and Islam: a perspective - Md Rosli, Ahmad Nabil; Sharip, Shalisah; Thomas, Nur Sakinah (Taylor & Francis, 2019)
Scrupulosity is characterized by an excessive anxiety against sinning and it is found to be common in Muslim societies. Spirituality plays a significant role in its presentation and management. The role of Islamic spirituality is examined by revealing the relevance of Islamic spiritual values e.g. acceptance (rida), patience (sabr), to the therapy. Five cases where these values are integrated into the therapy are described. Limitations on the available evidence are addressed. This study proposes the integration of these spiritual values, supports the use of psychotherapeutic discourse and contributes to the field of healthcare through practical conceptual applications in the therapy